Deconstructing Elon Musk's Rhetorical Prowess: A Pragmatic Analysis of Speech Acts in His TED Talk - Bahrani, Bahrani; Irawati, Dini; Hadijah, Sitti; Erangga, Suwarid (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
This research comprehensively analyzes Elon Musk's speech acts during his TED Talk Show episode